The Effect of Transformational Leadership and Digital Literacy on Civil Servant Performance: The Mediating Role of Adaptability at Regional Financial Management and Local Revenue Agency of Demak Regency - Fadhilah Prabandari; Yuliani Kadarini; Gita Sugiyarti (Proceeding of The International Conference on Business and Economics, 2026)
This study investigates the direct and indirect effects of transformational leadership and digital literacy on civil servant performance through the mediating role of adaptability. The research population comprised all 75 employees at the Regional Financial Management and Local Revenue Agency (BPKPAD) of Demak Regency, Indonesia. A saturated sampling method was employed, utilizing the entire population as respondents. Primary data were collected through structured questionnaires and analyzed using Structural Equation Modeling-Partial Least Square (SEM-PLS) with SmartPLS 3.3 software. The findings reveal that transformational leadership significantly and positively influences both civil servant adaptability and performance. Digital literacy demonstrates a significant positive impact on both adaptability and performance, emerging as the most dominant factor in the research model. Civil servant adaptability significantly and positively affects performance. However, mediation analysis indicates that adaptability does not significantly mediate the relationships between transformational leadership, digital literacy, and performance, suggesting that direct effects predominate over indirect effects in the BPKPAD Demak Regency context.